2021
DOI: 10.3390/ijerph18010341
|View full text |Cite
|
Sign up to set email alerts
|

Health(care) in the Crisis: Reflections in Science and Society on Opioid Addiction

Abstract: Opioid abuse and misuse have led to an epidemic which is currently spreading worldwide. Since the number of opioid overdoses is still increasing, it is becoming obvious that current rather unsystematic approaches to tackle this health problem are not effective. This review suggests that fighting the opioid epidemic requires a structured public health approach. Therefore, it is important to consider not only scientific and biomedical perspectives, but societal implications and the lived experience of groups at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The opioid epidemic remains a major public health crisis [1][2][3][4]. Despite increased attention and efforts to reduce opioid-related morbidity and mortality, the number of opioidrelated overdose deaths continues to rise [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The opioid epidemic remains a major public health crisis [1][2][3][4]. Despite increased attention and efforts to reduce opioid-related morbidity and mortality, the number of opioidrelated overdose deaths continues to rise [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Opioid abuse and addiction are not only medical problems that limit the clinical application of opioids but they also cause accidental death and many social problems (Damiescu et al., 2021; Ehrlich et al., 2019; United Nations Office on Drugs & Crime, 2020). Currently, methadone, buprenorphine, and naltrexone are mainly used to treat opioid addiction, but the existing treatment methods generally have shortcomings such as poor medication compliance and a high rate of relapse (Volkow et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the opioid epidemic is a complex public health problem that requires transdisciplinary approaches in order assure successful patient outcomes [8]. The first and hardest step in treating opioid misuse is going through the opioid withdrawal phase.…”
Section: Introductionmentioning
confidence: 99%